Patterns of interpopulation variation and physiological trade-offs of the acute thermal tolerance of juvenile Chinook salmon (Oncorhynchus tshawytscha) - Kenneth W. Zillig; Kenneth W. Zillig; Heather N. Bell; Alyssa M. FitzGerald; Alyssa M. FitzGerald; Nann A. Fangue (Frontiers in Fish Science)
IntroductionThe capacity of species and populations to respond to rapid environmental change will be pivotal for their resilience in the coming decades. To explore thermal plasticity, physiological trade-offs, and associations with environmental characteristics, we assessed the heat hardening response and acclimation capacity of juvenile Chinook salmon (Oncorhynchus tshawytscha) from seven hatchery populations spanning diverse ecoregions along the West Coast of the United States.MethodsProgeny from each population were acclimated to one of three temperatures (11, 16, or 20°C) and subjected to two acute thermal maximum (CTMAX) trials 24 h apart. The heat hardening response (ΔCTM) was calculated as the difference between an individual's second and first CTMAX trials. Acclimation capacity was determined as the maximum difference in CTMAX between fish acclimated to 11°C and 20°C during their second trial, capturing the full acclimatory scope. Bayesian models were employed to test the thermal trade-off hypothesis, which posits that individuals or populations with higher thermal tolerance have reduced capacity for acclimation. Trade-offs were analyzed at both individual and population scales. Associations between ΔCTM, acclimation capacity, and source population environmental characteristics were also examined using data from a landscape-scale, regional, river temperature model.ResultsFish acclimated to 16°C or 20°C exhibited heat hardening (positive ΔCTM), while those acclimated to 11°C exhibited “heat weakening” (negative ΔCTM), a rare phenomenon in the literature. At the individual level, fish adhered to the thermal trade-off hypothesis, with higher thermal tolerance associated with reduced plasticity. However, no such trade-off was observed at the population level. Acclimation capacity was positively correlated with latitude and the temperature of the natural rearing environment. Additionally, ΔCTM performance improved when fish were acclimated to temperatures closer to those of their natural habitats.DiscussionIndividual fish exhibited a trade-off between thermal tolerance and plasticity, while populations did not. Thermal plasticity was associated with environmental conditions, with populations from warmer habitats demonstrating greater acclimation and heat hardening capacities. This study highlights the importance of understanding interpopulation variation to identify at-risk populations, such as those from colder habitats or with limited thermal plasticity, like the Trinity population. These findings emphasize the need to account for interpopulation differences when predicting species responses to climate change and developing conservation strategies.